Avaliação de intervenções terapêuticas em pacientes com cicatrizes hipertróficas e queloides: revisão sistemática - Rebelo, Fabrizio Ricardo Cevallos [UNIFESP] (2021)
Introduction: The treatment of hypertrophic scars and keloids has been a challenge for medicine for decades, given that until now one has not yet found a treatment considered “Gold standard” due to the variety of therapies. Objective: The aim of the study was to analyze the different therapeutic interventions, whether single or associated, for the treatment of hypertrophic scars and keloids, from a systematic review. Method: PubMed, Web of Science, Scopus, EMBASE, Cochrane Library and Lilacs were searched, from January 1992 to April 2020, for randomized clinical trials of hypertrophic and keloid scar treatments, without restrictions of age, sex, race, or language limitation, which evaluated their effects with regard to height, erythema, flexibility, pigmentation, and Vancouver Scale. The review followed the recommendations of the PRISMA protocol, the tool to assess the risk of bias of the Cochrane was used, and the GRADE protocol. Mean differences (MDs), odds ratios (ORs) were calculated with 95% confidence intervals (CI), and a meta-analysis was performed. Results: Twenty-three studies were selected from 796, with a total of 1342 scars. Twelve studies included keloid and hypertrophic scars, while 11 only keloid scars. The analyzed interventions were the ones with use of Triamcinolone, Triamcinolone + 5-Fluorouracil, Verapamilo and Laser. There was no statistically significant difference in the effectiveness of any of the interventions in comparison to other therapies. Conclusions: This review demonstrated that there is no therapy more effective than another, be it individual or in association.